Trade openness and the demand for skills: evidence from Turkish microdata - Elena Meschi; Erol Taymaz; Marco Vivarelli (Institute for the Study of Labor (IZA), 2008)
In this paper we report evidence on the relationship between trade openness, technology adoption and relative demand for skilled labour in the Turkish manufacturing sector, using firm-level data over the period 1980-2001. In a dynamic panel data setting using a unique database of 17,462 firms, we estimate an augmented cost share equation whereby the wage bill share of skilled workers in a given firm is related to international exposure and technology adoption. Overall, results suggest that trade openness and technology play a key role in shifting the demand for labour towards more skilled workers within each firm. Technology-related variables (domestic R&D expenditures and technological transfer from abroad) are positive and significantly related to skill upgrading, as are the involvement of foreign capital in a firm's ownership and the propensity to export. Moreover, firms belonging to those sectors that most raised their imported inputs also experienced a higher increase in the labour cost share of skilled workers. This finding is consistent with the idea that imports by a middle-income country imply a transfer of new technologies that are more skill-intensive than those previously in use in domestic markets. This idea is reinforced by the finding that only imported inputs from industrialised countries - where the potential for innovation diffusion comes from - enter the estimated regression significantly.
urn:nbn:de:101:1-2008121997
Keywords: F16; O15; O33; 330; Globalisation; skills; skill-biased technological change; technology transfer; GMM-SYS; Außenhandelsliberalisierung; Arbeitsnachfrage; Qualifikation; Angepasste Technologie; Schätzung; Türkei